THE IMPLEMENTATION OF POLITICAL WOMEN’S RIGHTS IN STATE OF REPUBLIC INDONESIA WOULD BE HAVE DEMOCRACY - NANY SURYAWATI (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The State of the Republic of Indonesia is a rule of law based on democracy, and as outlined in its Constitution, the 1945 Constitution of the Republic of Indonesia, which has been amended gradually from 1999 to 2002. This amendment brought about fundamental changes to the building of the Indonesian state structure, particularly in fulfillment of the rights of citizens, in the political field, without distinction. Political human rights for Indonesian women are further emphasized in various laws and regulations. These human rights in the field of women’s politics have not experienced a significant increase, so that the representation of women in parliament, has not been evenly distributed, because it is still dominated by men. The existence of affirmative action that is fought for continuously makes the distribution of women’s representation in the management of political parties and in parliament close to the number of male representatives.The representation of Indonesian women has experienced ups and downs since the first general election in 1955, but with the amendment to the 1945 Constitution of the Republic of Indonesia, an activity is needed to socialize the understanding of democracy and politics for Indonesian women and also men, so support for involvement Indonesian women in politics are not only from the government but from all Indonesian people, so that the political rights of every Indonesian citizen can be fulfilled, at the same age as the goal of the Indonesian rule of law.